STRATEGI PUBLIC RELATIONS PT BIO HUTANEA CORP DALAM MEMPUBLIKASIKAN INFORMASI KEPADA PUBLIK EKSTERNAL - Leliana, Intan; Kurnia, Dea (Jurnal Public Relations (J-PR), 2020)
Currently information seekers can also find the information they want via the web, which is the web is one part of online media. Online media is now the best choice for the general public to find the information they need. This is where the role of Public Relations is needed to provide information to the public. The role of Public Relations in using the website to publish information really needs to be considered. In terms of publishing information, PT Bio Hutanea Corp also does not forget to be careful in conveying information so that there is no mistake in understanding the delivery to the external public. The external public itself is a connector or intermediary between the outside public and the company in order to create mutually beneficial things. In conducting this research, the writer used a qualitative descriptive research method, namely by making observations and interviews with the parties concerned. Then the collected data were analyzed descriptively by using the research results in the form of a research report. It can be concluded that since PT Bio Hutanea Corp has a website, there has been an increase in customers contacting, products and services sold have increased compared to before the website was created. Many customers decide to buy products and use services and cooperate with PT Bio Hutanea Corp. Broadly speaking, the PT Bio Hutanea Corp website has succeeded in attracting consumer interest. In this case, it can also help companies build good relationships with customers and increase links for the welfare of the company either by working with private and government companies. Keywords: Online Media, Website, Public Relations